ASSET BASED COMMUNITY DEVELOPMENT AS A METHOD TO STRENGTHEN ASEAN ECONOMIC COMMUNITY - Wicaksono, Setiawan (Indonesian Journal of International Law, 2015)
Indonesia as ASEAN member already binds to ASEAN Economic Community as consequences of Indonesia membership. It means, Indonesia have to apply the liberalization in goods trade whether for import goods or for export goods. As a goal and based on the goal set up by ASEAN Economic Community, the single market should be the way to prosperous people economic. The question is how to achieve this goal instead of pushing or destroying local goods from export goods. It needs to straight up the vision, back to previous goal, and take action to strengthen power or advantages from goods and from AEC system. One of the ways to achieve it is with Asset Based Community Development. This paper will analyze Asset Based Community Development as a means to strengthen ASEAN Economic Community. In Part I, this paper will examine the concept of ASEAN Economic Community. Part II will analyze further on what are the steps of Asset Based Community Development required in intensifying ASEAN Economic Community, and Part III is conclusion.